Floristic Inventory in a Forest Threatened by Agricultural Expansion in the Reserve of Los Chocuacos Tourism Center, Costa Rica - Cedeño-Fonseca, Marco (2020)
[Introduction]: The expansion of african palm (Elaeis guineensis) and pineapple (Ananas comosus) monocultures in Costa Rica, has progressively degraded the natural environment of the country, standin[i]g out, the region of the Potrero Grande district of Buenos Aires. [Objective]: This study, aims to show the importance of conservation in the Centro Turistico Los Chocuacos (CTLC) reserve, which is a threatened area, and that conserves a forest, between secondary and primary, of approximately 30 years.  [Methodology]: In an area of 25 hectares (ha), a floristic inventory was performed by random walks along the forest edge, trails, river, waters springs, and areas not crossed by trails. The botanical specimens were collected in a reproductive state, which were botanized and deposited in the Herbarium Luis A. Fournier Origgi of the University of Costa Rica. [Results]: The CTLC reserve has a floristic wealth of 75 families, 219 genera and 266 species. The results yield important data, such as, a new record for Costa Rica, Eugenia veraguensis, and a species of the genus Aristolochia, that is currently being described as new specie for science. The most representative life form is tree and the habit is mostly terrestrial. The Fabaceae, Rubiaceae and Malvaceae families were the most representative in the study area. [Conclusions]: The study highlights the importance of floristic inventories to increase knowledge of species present in poorly studied areas of the tropics that are also being affected by the disorderly land use change.